Stereo- and Enantioselective Addition of Organolithiums to 2-Oxazolinylazetidines as a Synthetic Route to 2-Acylazetidines - Musci, Pantaleo; Colella, Marco; Fanelli, Flavio; Altomare, Angela; Pisano, Luisa; Carlucci, Claudia; Luisi, Renzo; Degennaro, Leonardo (Frontiers in Chemistry, 2019)
A new synthetic route to N-alkyl-2-acylazetidines was developed through a highly stereoselective addition of organolithiums to N-alkyl-2‐oxazolinylazetidines followed by acidic hydrolysis of the resulting oxazolidine intermediates. This study revealed an unusual reactivity of the C=N bond of the oxazoline group when reacted with an organolithiums in a non-polar solvent such as toluene. The observed reactivity has been explained considering the role of the nitrogen lone pair of the azetidine ring as well as of the oxazolinyl group in promoting a complexation of the organolithium, thus ending up with the addition to the C=N double bond. The high level of stereoselectivity in this addition is supported by DFT calculations and NMR investigations, and a model is proposed for the formation of the oxazolidine intermediates, that have been isolated and fully characterized. Upon acidic conditions, the oxazolidine moieties were readily converted into 2-acylazetidines. This synthetic approach has been applied for the preparation of highly enantioenriched 2-acylazetidines starting from chiral not racemic N‐alkyl-2‐oxazolinylazetidines.